Review of motor vehicle particulate emissions sampling and measurement: From smoke and filter mass to particle number - Giechaskiel, Barouch; Maricq, Matti; Ntziachristos, Leonidas; Dardiotis, Christos; Wang, Xiaoliang; Axmann, Harald; Bergmann, Alexander; Schindler, Wolfgang (Journal of aerosol science, 2014)
Particulate emissions from motor vehicles have received increased attention over the past two decades owing to associations observed between ambient particulate matter (PM) levels and health effects. This has led to numerous changes in emissions regulations worldwide, including more stringent standards, the broadening of these to include non-road engines, and the adoption of new metrics. These changes have created a demand for new instruments that are capable of real time measurement, enhanced sensitivity, and on-board vehicle operation. In response, researchers and instrument manufacturers have developed an array of new and improved instruments and sampling methods. It is generally recognized that the exhaust aerosol concentration measured depends on both the sampling technique and the instrument used. Hence, many of the new instruments are complementary and offer merits in measuring a variety of particulate emissions attributes. However, selecting the best instrument for each application is not a straightforward task; it requires on one hand a clear measurement objective and, on the other, an understanding of the characteristics of the instrument employed. This paper reviews how vehicle exhaust particulate emission measurements have evolved over the years. The focus is on current and newly evolving instrumentation, including gravimetric filter measurement, chemical analysis of filters, light extinction, scattering and absorption instruments, and instruments based on the electrical detection of exhaust aerosols. Correlations between the various instruments are examined in the context of steadily more stringent exhaust emissions standards. The review concludes with a discussion of future instrument and sampling requirements for the changing nature of exhaust aerosols from current and future vehicles. •Vehicle exhaust particulate emissions regulation: not only type approval, but also on-board, in-use compliance and smoke for roadworthiness tests.•Current and newly evolving particulate instrumentation and conditioning techniques.•Correlations of particulate instruments in the context of steadily stringent particulate emissions standards.•Matching of measurement methods with measurement needs.